Dampak Krisis Ekonomi Terhadap Kinerja Sektor Perbankan- Analisis Perbandingan Bank Konvensional dan Syariah di Negara-Negara OKI - Saipul Arni Muhsyaf (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
This study investigates the impact of three significant economic crises—the Eurozone Debt Crisis (2010-2012), the COVID-19 Pandemic (2020-2021), and the Post-Pandemic Economic Recovery (2021-2022)—on the performance of conventional and Islamic banks in Organization of Islamic Cooperation (OIC) countries. Using a dataset of 4,381 observations from 34 OIC countries, panel regression techniques are employed to evaluate the influence of these crises on key financial performance metrics: Return on Shareholders' Funds (ROSF), Profit Margin (PM), Return on Total Assets (ROA), Current Ratio (CR), and Solvency Ratio (SR). The analysis reveals that while the Eurozone Debt Crisis did not significantly affect bank performance, the COVID-19 pandemic led to a notable decline in profitability but an improvement in liquidity. The results highlight that during the COVID-19 pandemic, banks faced substantial challenges in maintaining profitability, as evidenced by the significant decrease in PM. However, the improvement in CR suggests that banks enhanced their liquidity management strategies to cope with the crisis. The Post-Pandemic Economic Recovery phase brought positive changes in both profitability and liquidity, demonstrating the ability of banks to adapt and thrive as economic conditions stabilized. Macroeconomic variables, such as GDP growth and inflation, played crucial roles, with GDP growth positively affecting ROSF and inflation negatively impacting PM. These findings underscore the importance of a diversified banking system, including both conventional and Islamic banks, to enhance financial stability. Policymakers and financial regulators should consider the unique strengths of Islamic banking principles in regulatory frameworks and prioritize sound macroeconomic policies to promote stability and resilience in the banking sector. Future research should further explore the long-term impacts of economic crises on bank performance across different regions and banking models, as well as the interaction between regulatory environments and bank resilience. Keywords: Economic crises, bank performance, conventional banks, Islamic banks, OIC countries, COVID-19 pandemic, Eurozone Debt Crisis, post-pandemic recovery, financial stability, macroeconomic factors.